The effect of Ag electromigration on the properties of BiPbSrCaCuO superconductors - Dzhafarov, TD; Yilmazlar, M (ELSEVIER SCIENCE BV, 1997)
The effect of an electric field on the diffusion of silver and compounds (Cu and Sr) of BiPbSrCaCuO ceramic superconductors was investigated by energy-dispersive X-ray spectroscopy (EDX), it was established that Ag migrates in the electric field in the form of positively charged ions with effective charge q = +0.9 +/- 0.2., The electric field also stimulates redistribution of the matrix ions Cu and Sr in the cathode direction. Effects of Ag, Cu and Sr electromigration on crystal structure, composition, surface morphology and superconducting properties of the near-anode and the near-cathode region of BiPbSrCaCuO samples have been studied by X-ray diffraction (XRD), scanning electron microscopy (SEM) and resistivity measurements. It is found that electromigration of Ag and components of BiPbSrCaCuO is accompanied by the formation of predominantly the Bi-2223 phase and by an increase of the critical temperature on the cathode side in comparison with that on the anode side of the sample. (C) 1997 Elsevier Science B.V.
Keywords: ELECTRIC-FIELD; THIN-FILMS; DIFFUSION; Physics